1997
DOI: 10.1017/s0950268896007194
|View full text |Cite
|
Sign up to set email alerts
|

A fifteen month study of Escherichia coli O157:H7 in a dairy herd

Abstract: A dairy herd associated with Escherichia coli O157 infection in humans was studied for the 15 months following the outbreak to examine seasonal, age and management factors affecting faecal excretion of the organism and to determine the mode and frequency of milk contamination with the organism. Between May 1993 and July 1994, 28 visits were made to the farm to collect a total of 3593 rectal swabs from cows, heifers and calves and 329 milk samples. E. coli O157:H7 was isolated from 153 (4.3%) of 3593 bovine rec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

26
184
2
1

Year Published

1999
1999
2008
2008

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 232 publications
(213 citation statements)
references
References 17 publications
(31 reference statements)
26
184
2
1
Order By: Relevance
“…EHEC O157 can be isolated from various animals such as cattle [2,4,5,8,9,12,16,23], sheep [6], deer [1], and so on. In particular, it is often isolated from faeces of cattle showing no clinical signs of disease.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…EHEC O157 can be isolated from various animals such as cattle [2,4,5,8,9,12,16,23], sheep [6], deer [1], and so on. In particular, it is often isolated from faeces of cattle showing no clinical signs of disease.…”
mentioning
confidence: 99%
“…In particular, it is often isolated from faeces of cattle showing no clinical signs of disease. It was reported that the prevalence of EHEC O157 in cattle was 0.2-28% in the United States [7,8,23], 1.9% in Australia [5], and 4.2-20% in Europe [2,4,9,16]. Therefore, cattle can harbour the organisms in their faeces and are regarded as a natural reservoir and source of infection [3].…”
mentioning
confidence: 99%
“…Generally, healthy domestic animals are important natural reservoirs of human STEC infection [6], and direct or indirect contact with animals and their products, such as feces and slurry, have been implicated in several human cases of STEC infection [7,12,20,31]. We genetically examined different types of STEC, isolated from four sheep [26].…”
Section: Discussionmentioning
confidence: 99%
“…Carriage of E. coli 0157 by the cattle in the herd was monitored over the IS-month period immediately following the outbreak to examine seasonal, age and management factors affecting faecal excretion of the organism (Mechie et al 1997). Between May 1993 and July 1994, 26 visits were made to the farm to collect a total of 3593 rectal swabs from cows, heifers and calves and 329 milk samples.…”
Section: Unpasteurized Milk As a Source Of Infection In 1993mentioning
confidence: 99%